2015
DOI: 10.1515/jbcpp-2014-0054
|View full text |Cite
|
Sign up to set email alerts
|

Identification and evaluation of potentially inappropriate medications (PIMs) in hospitalized geriatric patients using Beers criteria

Abstract: The study shows high prevalence of prescribing PIMs in hospitalized elderly patients; PIM also caused incidence of ADEs; and serious drug-drug interactions were scarce among the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 20 publications
1
18
1
1
Order By: Relevance
“…The pharmacist investigator had worked together with the physicians for 5 years and this familiarity could explain the high rate of acceptance and correction of the PIMs identified in this study. The rate of PIMs identified in the present study (33.3%) was less than that reported in an Indian hospital for patients who had been prescribed at least one PIM (106/200; 53%) …”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…The pharmacist investigator had worked together with the physicians for 5 years and this familiarity could explain the high rate of acceptance and correction of the PIMs identified in this study. The rate of PIMs identified in the present study (33.3%) was less than that reported in an Indian hospital for patients who had been prescribed at least one PIM (106/200; 53%) …”
Section: Discussioncontrasting
confidence: 85%
“…The rate of PIMs identified in the present study (33.3%) was less than that reported in an Indian hospital for patients who had been prescribed at least one PIM (106/200; 53%). 6 The effectiveness of interventions by clinical pharmacists to optimise prescribing has been reported previously. 7,8 In their study, Lipton and Bird assessed the effects of clinical pharmacists' consultations on drug regimens, adherence and healthcare services for discharged older people: pharmacists consulted with older people at discharge and continued the intervention for 3 months, communicating with physicians as needed.…”
Section: Discussionmentioning
confidence: 84%
“…24,25 Prevalence of PIM use among hospitalized older adults in the present study was found to be 32.14% which is higher than that reported in some prospective studies in India by Zaveri HG et al 23 (23.5%), Harugeri A et al 24 (23.5%), Kashyap M et al 26 (21%), Shah KN et al 27 (29.3%), Pradhan S et al 28 (21.86%) and Vishwas HN et al 29 (24.6%). While some prospective studies showed higher prevalence of PIM use [Danisha P et al 30 (53%) and Momin TG et al 31…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, all these criteria seem to be appropriate in countries worldwide. Several studies have already used and adapted Beers and STOPP for different settings, including Brazil . Furthermore, no list of PIMS for older adults has yet been developed in Brazil …”
Section: Discussionmentioning
confidence: 99%